Halophila siaochihkanensis (Hydrocharitaceae), a new species from Penghu County, Taiwan - Pi-Jen LIU; Chiao-Wen LIN; Hsing-Juh LIN; Wei-Jen LIN; Li-Te HSIEH; Cheng-Xuan CAI; Ming-Yang HONG; Pei-Luen LU (TAIWANIA, 2025)
Halophila siaochihkanensis P.-L. Lu ＆ P.-J. Liu (Hydrocharitaceae) is described and illustrated as a new species from Penghu County, Taiwan. It is morphologically similar to Halophila ovalis (R. Br.) Hook. f. and Halophila decipiens Ostenf., but differs in flowering time, leaf hairs, and vegetative life history, having smaller leaves and fewer leaf veins, flowers with white to light yellowish brown tepals, shorter stamens, and fruits that are smaller, globose, and including several seeds in a fruit. This study explores the phylogenetic analysis of 11 species representing all four genera with two outgroup species using DNA Internal transcribed spacer (ITS). The dataset was analyzed using parsimony and maximum likelihood analysis. Results show that Halophila siaochihkanensis is monophyletic group. The species is morphologically and phylogenetically distinct from the remaining seagrass species in Taiwan and is recognized as a new species, Halophila siaochihkanensis P.-L. Lu ＆ P.-J. Liu, and a new key for seagrass of Taiwan is made.